2021
DOI: 10.1111/pcmr.12982
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of non‐syndromic and syndromic oculocutaneous albinism in human and mouse

Abstract: Oculocutaneous albinism (OCA) is the most frequent presentation of albinism, a heterogeneous rare genetic condition generally associated with variable alterations in pigmentation and with a profound visual impairment. There are non‐syndromic and syndromic types of OCA, depending on whether the gene product affected impairs essentially the function of melanosomes or, in addition, that of other lysosome‐related organelles (LROs), respectively. Syndromic OCA can be more severe and associated with additional syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 148 publications
0
36
0
3
Order By: Relevance
“…Mutations in Bloc1s5 [ 28 , 29 ] and Dtnbp1 [ 30 , 31 ] have been reported to cause pigment dilution in both eyes and coat, prolonged bleeding time and inner ear abnormalities. The human homologs, BLOC1S5 and DTNBP1 , are known to be causal genes for Hermansky-Pudlak Syndromic albinism types 11 and 7, respectively [ 32 ]. In normal mouse melanocytes, it has been reported that MITF and TFAP2A proteins bind together to the enhancer element in the intron 4 of interferon regulatory factor (4 Irf4 ) and cooperatively regulate Irf4 expression, resulting in activation of Tyr expression and thus normal pigmentation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in Bloc1s5 [ 28 , 29 ] and Dtnbp1 [ 30 , 31 ] have been reported to cause pigment dilution in both eyes and coat, prolonged bleeding time and inner ear abnormalities. The human homologs, BLOC1S5 and DTNBP1 , are known to be causal genes for Hermansky-Pudlak Syndromic albinism types 11 and 7, respectively [ 32 ]. In normal mouse melanocytes, it has been reported that MITF and TFAP2A proteins bind together to the enhancer element in the intron 4 of interferon regulatory factor (4 Irf4 ) and cooperatively regulate Irf4 expression, resulting in activation of Tyr expression and thus normal pigmentation [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1996, the HPS1 gene was identified as the causative gene of HPS‐1 by positional candidate cloning (Oh et al, 1996). Thereafter, other 10 HPS genes and their counterparts in mice have been identified as the genes for HPS‐2 to HPS‐11 subtypes (Fernandez et al, 2021). Moreover, at least four additional HPS genes in mice ( Bloc1s4 / Cno , Vps33a , Rab38 , Rabggta ) have been characterized (Table 1).…”
Section: Hps Genes and Associated Protein Complexesmentioning
confidence: 99%
“…Hermansky–Pudlak syndrome (HPS) is an autosomal recessive Mendelian disorder characterized by oculocutaneous albinism (OCA) or ocular albinism (OA), bleeding tendency, and ceroid deposition (Hermansky & Pudlak, 1959; Huizing et al, 1993; Wei & Li, 2013). Currently, 11 subtypes (HPS‐1 to HPS‐11) have been molecularly characterized in humans and at least 15 subtypes in mice have been described (Table 1) (Fernandez et al, 2021; Wei & Li, 2013). The hallmark of HPS pathogenesis is the defects in multiple tissue‐specific lysosome‐related organelles (LROs) (Table 2) (Delevoye et al, 2019; Wei & Li, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Massive amounts of biochemical and physiological data have been collected from TYR and TYRP1 loss of function models both in cultured cells and in animal models, for review [13,21,22]. By contrast, the impact of loss of function of DCT on pigmentation and even more so on ocular development has not been explored in such details.…”
Section: Introductionmentioning
confidence: 99%